Unveiling Subsurface Characteristics of Cliff Land in Sibang, Bali Through Geoelectric Investigation - Diana, Nur Ayu; Mareta, Ganeca Efa (UKaRsT, 2024)
The unique geological formations and environmental dynamics of cliffs underscore the significance of comprehending soil composition and structural integrity for diverse applications, such as infrastructure development and environmental conservation. Geoelectrical needs to be done because the underground geological conditions of the cliff must be researched and assessed first before construction is carried out so that construction failure does not occur. This research aims to reveal the subsurface characteristics of cliff soil in Sibang, Bali through geoelectrical investigation. This research was conducted by evaluating the soil condition in the field using the geoelectric resistivity method to the ability of a material to inhibit the flow of electric current and geological regional theories. At points BL-01 and BL-04, there is a significant potential risk of landslides due to the thick layer of breccia, especially during high rainfall or additional loads in the area. Point BL-02 also has a potential risk of landslides due to the thick layer of basalt and wet sand. Meanwhile, points BL-03 and BL-05 are more ideal locations for construction because they consist of relatively stable hard rock. Point BL-06 outside the development zone has layers of gravel, weathered tuffa and andesite which could be considered for future development. Thus, a deep understanding of the geological characteristics of each point is important to manage risks and ensure the safety and sustainability of construction projects in that area.